THE EFFECT OF ACCEPTED EASE OF USE AND SATISFACTION ON THE INTENTION OF THE CONTINUITY OF THE LEARNING MANAGEMENT SYSTEM. - Bagaskara, Bima; Yohana, Corry; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine whether the variable Perceived ease of use, satisfaction affects the continuance intetion of Google Classroom users at the State University of Jakarta. A total of 200 respondents or students from Jakarta State University were obtained by survey method using Google Form and using Likert Type by purposive sampling. By using the Structural Equation Modeling (SEM) method, the results show that Perceived ease of use has a positive and significant effect on satisfaction and continuance intetion and satisfaction has a positive and significant effect on continuance intetion with Plabel value < 0.050 and C.R value > 1960.